2013
DOI: 10.1007/s13659-013-0034-7
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of 1-oxomiltirone via Suzuki coupling

Abstract: Abietane diterpenes and miltirone series have shown important activities and for medical purposes in order to achieve the total synthesis of 1-oxomiltrone 1 and miltirone 4, a versatile intermediate 6 was found. The compound 6 could be used as a precursor A-B-C rings with different oxidative degrees in selected abietane diterpenes when synthesized through high yield Suzuki reaction and subsequent cyclization, and total synthesis of 1-oxomiltirone (1) has been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Our synthesis commenced with coupling reaction of arylboronic acid 8 [15]. Commercially available 3-Me-cyclohexenone was treated with trifluoroacetic palladium and ( s )- t -BuPyOX ligand in heterogeneous solvent and 9 was isolated in moderate ee and 73 % yield [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our synthesis commenced with coupling reaction of arylboronic acid 8 [15]. Commercially available 3-Me-cyclohexenone was treated with trifluoroacetic palladium and ( s )- t -BuPyOX ligand in heterogeneous solvent and 9 was isolated in moderate ee and 73 % yield [32].…”
Section: Resultsmentioning
confidence: 99%
“…These findings have, in return, promoted the development of efficient synthesis strategy. We seek to discover new lead compounds, especially from nature terpenoids, for the development of anticancer drug [1517]. Hence, TP is a valuable target for us to investigate SAR of tri-epoxide.…”
Section: Introductionmentioning
confidence: 99%
“…The abietane diterpenes have profound biological activities. These diterpenoids majorly display antibacterial, anti‐inflammatory, antioxidant, and cytotoxicity values [161,162] . The structural feature of the abietane diterpenoids is the presence of fused [6‐6‐6] tricyclic ring structures [163] .…”
Section: Gold‐catalyzed Total Synthesis Of Natural Productsmentioning
confidence: 99%
“…14,15 We also showed that the Au-catalyzed reaction on diynals and enynals can be proceeded selectively by [4+2]-benzannulation or [3+2]-cycloaddition to give the corresponding 6-6-6-or 6-7-5-tricyclic skeleton depending the reaction conditions. 16 Taking into account the efficiency and capability to construct the complex tricyclic skeleton of this process, we report herein the total synthesis of 1-oxomiltirone 7,8 and arucadiol 17 ( Figure 1) by using [4+2]-benzannulation catalyzed by AuBr 3 or Cu(OTf) 2 . We envisioned that the 6-6-6-fused ring may prepare efficiently from key intermediate diynal 6 via only one cycloaddition step.…”
Section: Letter Synlettmentioning
confidence: 99%
“…Due to its complex structural characteristics as well as the interesting biological activity, synthesis of abietane natural products has been the object of several research groups. [5][6][7] Two main strategies have been applied for the synthesis of these compounds: (1) semisynthesis starting from natural product was performed to introduce the required functional group, 8 and (2) the 6-6-6-tricyclic core by cycloaddition/cyclization has been constructed.…”
mentioning
confidence: 99%